Expression of Iran isolate IBDV VP2 and VPX protein in prokaryotic expression system - Hosseini, Seyed Davood; Omar, Abdul Rahman; Ideris, Aini; Ali, Abdul Manaf (Universiti Putra Malaysia Press, 2004)
A serotype I very virulent infectious bursal disease virus (vvIBDV) isolated in Iran, SDH1 IBDV isolate, was subjected to express in prokaryotic system. The VP2 and VPX genes of the isolate were amplified by reverse transcription-polymerase chain reaction, cloned, sequenced and expressed in Escherichia coli system as a fusion protein with six-histidine tag. Protein bands with expected molecular weight of 48KD and 51KD were detected by directed protein staining and western blotting. These expressed protein can be considered as a candidate for serological tests instead of whole virion, and also provide a starting point in the design of alternatives to live IBDV vaccine for prevention of infectious bursal disease.